Analisis Pengaruh Penggunaan Limbah Cangkang Siput Pada Campuran Asphalt Concrete-Wearing Course (AC-WC) - Saifulloh, Reza; Rumbyarso, Yonas Prima Arga; S, Sukadi (Madani: Jurnal Ilmiah Multidisiplin, 2024)
Material that passes through No. 200 is used as a filler for asphalt concrete mixtures. The filler material used in this research is snail shells or mollusk shells which are often found in coastal waters. Because snail shell ash contains chitin (C8H13O5N) and lime (CaCO3), its characteristics are comparable to other fillers. The purpose of the filler is to make the asphalt thicker and less sensitive to temperature. The characteristics of the asphalt mixture can be influenced by the filler used in the Laston mixture. Excessive amounts of filler will cause the mixture to become stiff and crack easily. On the other hand, the mixture can become too soft if the filler level is too low. This research uses an experimental design at the Asphalt Laboratory, Faculty of Engineering, Krisnadwipayana University. Snail shell fillers of 0%, 15% and 30% were applied at different levels. The aim of this research is to determine the effect of Marshall characteristics on changes in the amount of snail shell waste used as a filler in the asphalt concrete layer mixture in the Asphalt Concrete-Wearing Course (AC-WC) layer. The research results show the highest value for optimum asphalt with stability of 2208 kg, flow 5 mm, VIM 33.6%, VMA 42.38%, VFA 99.8%, and Marshall Quotient 458 kg/mm, which meets the 2018 Bina Marga specifications.